Proximate Composition, Mineral and Phytochemical contents of whole fruits, rinds and seeds of Guna (Citrullus vulgaris) fruit. - Ndahi, T. E.; Badau, M. H.; Kassum, A. L.; Mshelia, L. P.; Peter, D. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
The consumption of fruit and vegetables contribute significantly to nutrient intake. However, the concentration of nutrients in whole fruits, rinds and seeds of a produce may differ. The objective of this study was to determine the proximate composition, minerals and phytochemical contents of guna (Citrullus vulgaris) whole fruits, rinds (peels) and seeds. The proximate composition (moisture, ash, protein, fat, fibre and carbohydrate), mineral contents (Ca, Mg, P, Fe, Na, K, and Zn) and Phytochemical contents (flavonoids, phenols, tannin, alkaloid, saponin, glycosides and steroids) of whole fruit, rinds and seeds of guna were determined using standard methods. The results show that moisture, ash, protein, fat, fibre, carbohydrate and energy contents ranged from 11.44-82.69%, 1.43 - 2.64%, 0.52-21.82%, 0.45-26.58%, 8.15-18.21%, 5.32-19.31% and 33.37 - 403.74Kcal/100g respectively. Additionally,guna seeds sample recorded the highest value in ash, protein, fat, fibre, carbohydrate and energy contents.Similarly, guna seeds was observed to have the highest Ca (5.52mg/100g), Mg (349.52mg/100g) and P (155.66mg/100g) contents while it has the least Fe (0.117mg/100g) and Na (18.74mg/100g) contents respectively. The phytochemical contents of whole fruits, seeds and rinds samples of guna differed significantly (p<0.05). The flavonoid, phenol, alkaloid, tannin, saponin and glycoside contents ranged from 6.23 - 55.18mg/100g, 4.61 - 38.11mg/100g, 642.69 - 785.12mg/100g, 0.52 - 44.79mg/100g, 15.75 - 131.79mg/100g and 0.068 - 0.255mg/100g respectively. Furthermore, guna seeds recorded the highest flavonoid, phenol, tannin and saponin contents and the least in glycoside content. The steroid content of guna seeds (62.05mg/100g) was higher than in the whole fruits (8.97mg/100g), and was not detected in guna rinds samples. Therefore, it could be concluded that guna seeds contained high protein, fat and energy values for nutrition compared to the whole fruits and rinds as well as relative high amount of mineral and phytochemical contents. Thus, guna seeds could be used for nutritional and therapeutic purposes.